Metering/payment/control systems (MPCS) for electric vehicles-I : meter design - Yeo, Kiat Keong. (2012)
An electric car is powered by an electric motor instead of a gasoline engine. Electric motor is being control by a controller, which regulates the amount of power—based on the driver’s use of an accelerator pedal. The electric car (also known as electric vehicle or EV) uses energy stored in its rechargeable batteries. The batteries are rechargeable by common household electricity supply.